Impact of thymoquinone supplementation on immobilisation stress-induced changes in reproductive characteristics of male mice - Abdul Rahman, Suzanah; Mohamed Anwar, Norul Athirah; Shaik , Sadak Basha; Kamarzaman, Saheera (Applied and Natural Science Foundation, 2014)
The aim of the current study was to investigate changes in the reproductive parameters during stress and the impact of thymoquinone during the period. The effects of stress were measured through immobilisation stress on mice. Group I was administered normal saline daily via intraperitoneal injection while Groups II and III were subjected to 2 and 6 hours of immobilisation stress respectively. Groups IV and V were subjected to stress for 2 and 6 hours respectively followed by intraperitoneal injection of 10 mg/kg thymoquinone which was continued on alternate days. The level of significance was set at p<0.05 and statistical analysis showed significant difference in testicular weight of mice in groups II and III compared to the controls but no significant difference was obtained for sperm count between all groups. Sperm motility, however, was significantly different among the groups under stress for 2 and 6 hours and that of 6 hours with the treatment of thymoquinone when compared to the controls. The histology of the testes also indicated a few alterations in comparison to the controls in the germinal epithelium and spermatogenic pattern in groups III and V.